2006
DOI: 10.1089/thy.2006.16.949
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Supplementation for Pregnancy and Lactation—United States and Canada: Recommendations of the American Thyroid Association

Abstract: The fetus is totally dependent in early pregnancy on maternal thyroxine for normal brain development. Adequate maternal dietary intake of iodine during pregnancy is essential for maternal thyroxine production and later for thyroid function in the fetus. If iodine insufficiency leads to inadequate production of thyroid hormones and hypothyroidism during pregnancy, then irreversible fetal brain damage can result. In the United States, the median urinary iodine (UI) was 168 microg/L in 2001-2002, well within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
115
0
16

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(133 citation statements)
references
References 9 publications
2
115
0
16
Order By: Relevance
“…The present study also indicates that the median IUC was significantly higher in the second and third trimesters, which could be attributed to the intake of iodinecontaining supplements. However, the intake of iodine Table 3 The association between dietary factors and participants' characteristics and logarithmically transformed UIC (μg/g Cr) in multiple linear regression analysis; nationally representative sample of pregnant women (n 683), Latvia, 2013 supplements containing 150 µg iodine, as recommended by the American Thyroid Association (29) , did not explain that association and also did not appear to be more effective in reducing the iodine deficiency during pregnancy. This might be attributed to the fact that in our study there was an insufficient number of women taking supplements containing ≥150 μg iodine to find the difference between subgroups statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The present study also indicates that the median IUC was significantly higher in the second and third trimesters, which could be attributed to the intake of iodinecontaining supplements. However, the intake of iodine Table 3 The association between dietary factors and participants' characteristics and logarithmically transformed UIC (μg/g Cr) in multiple linear regression analysis; nationally representative sample of pregnant women (n 683), Latvia, 2013 supplements containing 150 µg iodine, as recommended by the American Thyroid Association (29) , did not explain that association and also did not appear to be more effective in reducing the iodine deficiency during pregnancy. This might be attributed to the fact that in our study there was an insufficient number of women taking supplements containing ≥150 μg iodine to find the difference between subgroups statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Interpretation of thyroid function tests should be trimester-specific, 28,47,48 and locally generated trimester-specific reference levels should be applied when available. 47,49 Of note, it has been reported that the upper 95% Cl for plasma TSH in the first trimester is 2.5 mU=L. 47 It is known that the TSH level descends 60%-80% by week 10 and recovers slowly thereafter, but it may not reach the preconception normal range until gestation ends.…”
Section: Diagnosis Of Suspected Diseasementioning
confidence: 99%
“…During pregnancy and breastfeeding, women should increase their daily iodine intake to 250 mg daily. 46,49,59 LT 4 therapy is needed if, despite the iodine supplementation, abnormal serum TSH levels are detected.…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…To support fetal and infant thyroid function, the Institute of Medicine suggests an RDA for pregnant women of 220 lg iodine per day and 290 lg iodine per day during breastfeeding (10). To prevent iodine deficiency, the American Thyroid Association recommends supplementation containing 150 lg of iodine daily for U.S. women of childbearing age during the preconception phase, as well as during pregnancy and lactation (11). In addition, adequate iodine intake before conception (RDA of 150 lg per day) is important to ensure adequate maternal iodine stores to support the fetus.…”
Section: Introductionmentioning
confidence: 99%